PERILAKU MASYARAKAT TERHADAP SANITASI TOTAL BERBASIS MASYARAKAT DI KABUPATEN MAJENE - Abdul Ganing; Miftah Chairani (Politeknik Kesehatan Kemenkes Mamuju, 2016)
There is 89.02% urban/rural yet On Defecation Free (ODF) in Regional of Majene. Factors affecting the formation of village ODF is community behavior. The aim of this study was to describe behavior of society (knowledge, attitudes, and actions) towards the establishment of ODF village in Regional of Majene. Qualitative research methods carried out in Tande Timur and Adolang Dhua Village with descriptive design. The number of informants as many as 29 people (22 people informant ordinary and 7 key informants). Data processing begins with coll (place holder) ecting the results of the interview are processed, according to the studied variables and the contents analyzed and presented in manuscript form. The research result shows that the knowledge, attitudes and actions of people is good and supports the formation of ODF in the Village of Tande Timur. Knowledge and attitudes of people in the village Adolang Dhua is good yet the action not support to become ODF village.